‘Toward a Global Social Contract for Trade’ - a Rawlsian approach to Blockchain Systems Design and Responsible Trade Facilitation in the New Bretton Woods era - Arnold Lim; Enrong Pan (Journal of Responsible Technology, 2021)
Imminent changes to the international monetary system alongside a shift toward more egalitarian principles of justice in commercial contracts for trade are now taking place. Such changes however do not sufficiently account for circumstances of hardship, or black-swan events such as COVID-19, whereby the relative losers of trading arrangements should continue to receive outcomes which are not only efficient, but also fair and resilient. We argue that the ‘Society-in-the-Loop’ (SITL) social contract paradigm, in conjunction with the use of Strategic Responsible Innovation Management (StRIM), can together provide a solution for improving distributive justice in trade. Through collaboration with a locally based trade facilitation company, we describe the innovation-planning phase of a blockchain smart contract solution based on Derek Leben's idea of a ‘Rawlsian Algorithm’ (2017). It is demonstrated how this can be used to strengthen the algorithmic fairness of commercial contract implementation in accordance with existing ISO 20022 standards. Since currently no formal design framework exists for modeling blockchain oriented software (BOS), an agile development approach is adopted which takes account of the substantial difference between traditional software development and smart contracts. This method involves the construction of UML Use Case, Sequence, and Class diagrams, with a view to blockchain specificities. Evaluation and feedback from the company is also considered.